Entrustable professional activities, emergency medicine and medical education: a systematic review - Lopes, Lucas Casagrande Passoni (2024)
Introduction: Entrustable professional activities (EPAs) are one way to assess competencies, and are designed to bridge the gap between theoretical competencies and real world clinical practice. Aims: This was a systematic review which aims to answer the question: “Which EPAs related to Emergency Medicine are described for medical schools?”. Methods: We included original qualitative, interventional and observational studies (cross-sectional, case-control, and cohort studies) that described EPAs relevant to Emergency Medicine for Medical School. The search strategy was created using a combination of keywords and standardized index terms related to EPAs and Emergency Medicine. Results: The search strategy identified 991 citations. After screening the titles and abstracts, we identified 85 potentially relevant studies. After the full-text review, a total of 11 reports met the criteria for inclusion. Conclusion: Recognizing a patient requiring urgent or emergent care and initiating evaluation and management is the most common EPA related to Emergency Medicine described at Medical Schools. Use of EPAs is associated with increased student satisfaction and improved competences. However, there is a lack of undergraduate EM specific EPAs being systematically developed and published, and this should be an area to be explored in future studies.